Cardiosphere-derived cells, with and without a biological scaffold, stimulate myogenesis and recovery of muscle function in mice with volumetric muscle loss. (July 2021) - Rogers, Russell G.; Li, Liang; Peck, Kiel; Sanchez, Lizbeth; Liu, Weixin; Ciullo, Alessandra; Alfaro, Jocelyn; Rannou, Alice; Fournier, Mario; Lee, Yena; Marbán, Eduardo
Abstract: Extremity trauma to military personnel and civilians commonly results in volumetric muscle loss (VML), leaving patients suffering chronic physical disability. Biomaterial-based technologies such as extracellular matrices (ECMs) are currently in clinical testing for soft tissue repair, but, in preclinical models of VML, the efficacy of ECMs is equivocal. In a murine model of VML, we investigated the effects of ECM and/or cardiosphere-derived cell (CDC) therapy; the latter improves skeletal myogenesis and muscle function in mdx mice, so we reasoned that CDCs may exert disease-modifying bioactivity in VML. While ECM alone improves functional recovery, CDCs have no additive or synergistic benefits with ECM transplantation following VML injury. However, CDCs alone are sufficient to promote muscle recovery, leading to sustained increases in muscle function throughout the study period. Notably, CDCs stimulate satellite cell accumulation in the muscle defect area and hasten myogenic progression (as evidenced by qPCR gene expression profiling), leading to global increases in myofiber numbers and anterior muscle compartment volume. Together, these data implicate CDCs as a viable therapeutic candidate to regenerate skeletal muscle injured by VML.